Pandangan Masyarakat Buddha Terhadap Wawasan Buddhayana Dalam Konteks Komunikasi Sosial - Agustin, Drian; Kosasih, Ananda; Linardy, Yanuar; Enrico, Albert; Adi Gautama, Sidartha (Kajian dan Reviu Jinarakkhita: Jurnal Gerakan Semangat Buddhayana (Jinarakkhita Review & Studies: Journal of Buddhayana Spirit Movement), 2023)
Indonesia is the world's largest archipelago located in Southeast Asia. It borders some countries in Southeast Asia and Oceania. Indonesia has a diversity of cultures, races, ethnicities, beliefs, religions, and languages. The religions that exist in Indonesia are Christianity, Catholicism, Confucianism, Hinduism, Islam, and Buddhism. Buddhism in Indonesia has developed because of the Buddhayana figures who are very meritorious so we can understand the teachings of Budhayana until now. One of the most influential figures in the development of Buddhism in modern Indonesia is Bhikkhu Ashin Jinarakkhita, better known as Su Kong who was the first person in Indonesia to be ordained as a sangha member after 500 years of the collapse of the Majapahit kingdom in 1953. He brought the concept of Sang Hyang Adi Buddha or the concept of divinity to Indonesia so that Buddhism could be legally recognized in the law. One of the teaching concepts he learned was the concept of Buddhayana. In its development, Buddhayana itself has gone through various dynamics and challenges from various circles of Buddhist society in Indonesia. However, the Buddhayana Movement succeeded in uniting various patterns of Buddhist society. Some of these styles, such as Mahayana, Theravada, and Tantrayana. The view of Buddhayana must be taught to Indonesian people who still do not have a broad insight into Buddhism and the view of Buddhayana itself